Soft magnetic powder and dust cores

By attaching a Nb and glass compound to Fe-Si alloy powder to form an insulating layer, the solution addresses hysteresis and eddy current losses in powder magnetic cores, improving energy efficiency and reducing heat generation.

JP7603759B2Active Publication Date: 2024-12-20TAMURA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023135530
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2024-12-20
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Existing powder magnetic cores face challenges in reducing hysteresis loss and eddy current loss, which are critical for improving energy efficiency and reducing heat generation in coil components used in various applications.

Method used

A compound consisting of Nb and glass is attached to the surface of Fe-Si alloy powder to form an insulating layer, which repairs the crystal structure and acts as an insulating film, thereby reducing hysteresis and eddy current losses.

Benefits of technology

The solution effectively reduces hysteresis and eddy current losses, leading to lower iron loss in powder magnetic cores, enhancing energy efficiency and reducing heat generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603759000006
    Figure 0007603759000006
  • Figure 0007603759000007
    Figure 0007603759000007
  • Figure 0007603759000008
    Figure 0007603759000008
Patent Text Reader

Abstract

To provide a soft magnetic powder capable of reducing hysteresis loss and eddy current loss, thereby reducing iron loss and to provide a dust core.SOLUTION: A soft magnetic powder comprises an Fe-Si-based alloy powder. On the surface of the Fe-Si-based alloy powder, a compound of Nb and glass with a melting point of 900°C or less is adhered. An average particle size of the Fe-Si-based alloy powder may be 13.76 μm or larger.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic powder and a dust core containing the soft magnetic powder. [Background technology]

[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core. Powder magnetic cores are often used for this core.

[0003] A powder magnetic core includes soft magnetic powder and an insulating layer formed around the soft magnetic powder, and the soft magnetic powder with the insulating layer formed thereon is compressed under high pressure of several tons to several tens of tons to produce a compact. The compact is then subjected to a heat treatment called annealing to produce a powder magnetic core.

[0004] Due to requirements for improved energy exchange efficiency and low heat generation, powder magnetic cores are required to have magnetic properties that minimize energy loss when magnetic flux density changes. The magnetic property related to energy loss is specifically iron loss (Pcv). Iron loss (Pcv) is expressed as the sum of hysteresis loss (Ph) and eddy current loss (Pe). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5929819 [Patent Document 2] JP 2017-098426 A Summary of the Invention [Problem to be solved by the invention]

[0006] Research has been conducted to reduce hysteresis loss. For example, as in Patent Document 1, research has been conducted to show that low hysteresis loss can be obtained when the crystal grains are coarse. In addition, as in Patent Document 2, research has been conducted to show that eddy current loss can be reduced by separating the core and the coil by a certain distance or more. However, in recent years, the applications of coil components have become more diverse, and there is an even greater demand for reducing hysteresis loss and eddy current loss, i.e., reducing iron loss.

[0007] The present invention has been made to solve the above problems, and an object of the present invention is to provide a soft magnetic powder and a dust core that can reduce hysteresis loss and eddy current loss and can reduce iron loss. [Means for solving the problem]

[0008] As a result of intensive research, the inventors have found that by attaching a compound formed by bonding Nb and glass to the surface of soft magnetic powder containing Fe-Si alloy powder, the crystal structure of the surface of the Fe-Si alloy powder can be restored to a regular structure by Nb, thereby reducing hysteresis loss, and that the glass acts as an insulating coating to reduce eddy current loss.

[0009] The present invention has been made based on the above findings, and the soft magnetic powder of the present invention includes an Fe-Si alloy powder and an insulating layer, and Nb and Phosphate Glass The insulating layer is formed of a compound formed by bonding the Nb and the Phosphate A compound consisting of glass bonds is formed on the surface of the Fe-Si alloy powder. The average particle size of the Fe-Si alloy powder is 13.76 μm or more in terms of median size D50, the amount of the compound added is 0.2 wt % or more and 0.6 wt % or less with respect to the Fe-Si alloy powder, and the content of Nb in the compound is 0.090 wt % or more and 0.27 wt % or less. It is characterized by the fact that

[0010] A dust core containing this soft magnetic powder is also one aspect of the present invention. Effect of the Invention

[0011] According to the present invention, it is possible to obtain a soft magnetic powder and a dust core that can reduce hysteresis loss and eddy current loss and can reduce iron loss. [Brief description of the drawings]

[0012] [Figure 1] 1 is a graph showing hysteresis loss in an example and comparative examples 1 and 2. [Diagram 2] FIG. 4 is a diagram showing the relationship between the average particle size of the soft magnetic powder and hysteresis loss. [Diagram 3] FIG. 4 is a diagram showing the relationship between the average particle size of the soft magnetic powder and eddy current loss. [Figure 4] FIG. 4 is a diagram showing the relationship between the average particle size of the soft magnetic powder and iron loss. [Diagram 5] FIG. 1 is a graph showing the relationship between the amount of a compound in which Nb and phosphate glass are combined and hysteresis loss. [Figure 6] FIG. 1 is a diagram showing the relationship between the amount of a compound formed by combining Nb with phosphate glass and eddy current loss. [Figure 7] FIG. 1 is a diagram showing the relationship between the amount of a compound in which Nb and phosphate glass are combined and iron loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The soft magnetic powder and the dust core according to the present embodiment will be described in detail below. Note that the present invention is not limited to the embodiment described below.

[0014] Powder cores are magnetic materials used as cores for coil components installed in office equipment, solar power generation systems, automobiles, etc. Powder cores are made of soft magnetic powder. A compound of niobium (hereafter referred to as Nb) and glass adheres to the surface of the soft magnetic powder. In addition, the soft magnetic powder to which the compound formed by combining Nb and glass adheres is coated with an insulating layer. The soft magnetic powder coated with this insulating layer is pressure-molded to produce a compact, which is then heat-treated to produce the powder core.

[0015] As the soft magnetic powder, Fe-Si alloy powder containing Si with iron as the main component is used. The Fe-Si alloy powder may be, for example, Fe-5.5%Si alloy powder containing 5.5wt% Si relative to Fe, or Fe-6.5%Si alloy powder containing 6.5wt% Si relative to Fe, but the ratio of Si to Fe may be other than 5.5% or 6.5%. The Fe-Si alloy powder may also contain Co, Al, Cr, or Mn. The particle size (median size D50) of the Fe-Si alloy powder is preferably 13.76 μm or more. By making the particle size 13.76 μm or more, the effect of reducing hysteresis loss by adhering Nb is significantly observed.

[0016] The Fe-Si alloy powder is preferably heat-treated in a non-oxidizing atmosphere such as a vacuum atmosphere or an inert gas atmosphere, or in the air, before the compound formed by bonding Nb and glass is attached. Examples of inert gas include H2 and N2. The heat treatment temperature is preferably 500°C or higher and 700°C or lower. By heat-treating the Fe-Si alloy powder in the temperature range of 500°C or higher and 700°C or lower, the hysteresis loss is reduced. The heat treatment time is about 2 hours.

[0017] A compound formed by bonding Nb and glass is attached to the surface of the Fe-Si alloy powder. This compound may be attached to the surface of each particle of the Fe-Si alloy powder, or to the surface of the particle aggregate, or both of these modes may be mixed. In addition, the compound formed by bonding Nb and glass may be attached so as to cover the entire surface of the particle or particle aggregate, or may be attached so as to cover a part of the surface of the particle or particle aggregate.

[0018] Although this is a speculation and not limited to this mechanism, it is believed that Nb attached to the surface of the Fe-Si alloy powder reduces hysteresis loss by repairing lattice defects in the crystals of the Fe-Si alloy powder. It is also believed that phosphate glass attached to the surface of the Fe-Si alloy powder acts as an insulating film, reducing eddy current loss.

[0019] By combining Nb with glass, which has a high affinity for metals, even a small amount of Nb can be efficiently attached to the surface of Fe-Si alloy powder. If a mixture of Nb powder and resin is added to Fe-Si alloy powder, the resin may adhere to the surface of the Fe-Si alloy powder, and Nb may not adhere. In other words, just because the mixture adheres does not necessarily mean that Nb adheres. The surface of Fe-Si alloy powder to which Nb does not adhere is not repaired, and the reduction of hysteresis loss may not be effectively achieved. In order to increase the possibility of attaching Nb to the surface of Fe-Si alloy powder, the content of Nb contained in the mixture must also be increased.

[0020] On the other hand, when the compound is made of Nb and glass as in the present invention, since the compound also contains Nb, Nb adheres to the surface of the Fe-Si alloy powder, and therefore Nb can be adhered to the surface of the Fe-Si alloy powder more efficiently than in the case of a mixture with Nb.

[0021] The glass to be used has a melting point of 900°C or less. For example, well-known glass such as phosphate glass can be used. By setting the melting point at 900°C or less, the glass softens during heat treatment of the powder compact, and the glass spreads more easily on the surface of the Fe-Si alloy powder. For example, when the heat treatment temperature of the powder compact is 650°C and the melting point of the glass is 900°C, and the heat treatment temperature and the melting point of the glass are far apart, it is possible to soften the glass by adjusting the heat treatment time.

[0022] The amount of the compound formed by combining Nb and glass is preferably 0.1 wt% or more and 0.6 wt% or less with respect to the Fe-Si alloy powder. The amount of Nb contained in this compound is preferably 0.045 wt% or more and 0.27 wt% or less. By setting the amount of the compound and the amount of Nb contained in the compound within this range, the hysteresis loss can be reduced.

[0023] More preferably, the amount of the compound formed by combining Nb and glass is 0.2 wt% or more and 0.6 wt% or less with respect to the Fe-Si alloy powder. The content of Nb contained in this compound is preferably 0.09 wt% or more and 0.27 wt% or less. By setting the amount of the compound and the content of Nb contained in the compound within this range, not only the hysteresis loss but also the eddy current loss can be reduced, and as a result, the iron loss is reduced.

[0024] After adding the compound formed by bonding Nb and glass, heat treatment is performed in a nitrogen atmosphere. The heat treatment temperature is preferably 350°C to 800°C. The heat treatment time is about 10 hours, but may be changed appropriately depending on the heat treatment temperature. When adding the compound formed by bonding Nb and glass, a known binder such as an acrylic binder may be added. The binder evaporates during this heat treatment, and may not adhere to the surface of the Fe-Si alloy powder, or may remain as a residue.

[0025] An insulating layer is formed on the outside of the Fe-Si alloy powder to which the compound formed by bonding Nb and glass is attached. That is, when the compound formed by bonding Nb and glass is attached so as to cover the entire surface of the particle or particle agglomerate, the insulating layer is formed on the surface of the compound formed by bonding Nb and glass, and when the compound formed by bonding Nb and glass is attached so as to cover a part of the surface of the particle or particle agglomerate, a part of the insulating layer is also formed on the surface of the Fe-Si alloy powder.

[0026] The insulating material constituting the insulating layer includes a silane coupling agent, a silicone oligomer, a silicone resin, or a mixture thereof. The insulating layer may be a single layer or multiple layers. For example, the insulating layer may be composed of multiple layers divided by type, or may be a single layer of one type or a mixture of two or more types of insulating materials.

[0027] As the silane coupling agent, aminosilane-based, epoxysilane-based, and isocyanurate-based silane coupling agents can be used, and in particular, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate are preferred. The amount of the silane coupling agent added is preferably 0.10 wt% or more and 1.0 wt% or less based on the Fe-Si alloy powder. By setting the amount of the silane coupling agent added within this range, the fluidity of the soft magnetic powder can be improved, and the density, magnetic properties, and strength properties of the molded powder core can be improved.

[0028] After the silane coupling agent is added, the mixture of the Fe-Si alloy powder and the silane coupling agent is heated and dried. The drying temperature is preferably 25°C to 200°C. If the drying temperature is lower than 25°C, the solvent may remain and the insulating coating may become incomplete. On the other hand, if the drying temperature is higher than 200°C, decomposition may progress and the insulating coating may not be formed. The drying time is about 2 hours.

[0029] As the silicone oligomer, methyl-based or methylphenyl-based ones having an alkoxysilyl group and no reactive functional group, epoxy-based, epoxymethyl-based, mercapto-based, mercaptomethyl-based, acrylic methyl-based, methacrylic methyl-based, vinylphenyl-based ones having an alkoxysilyl group and a reactive functional group, or alicyclic epoxy-based ones having a reactive functional group instead of an alkoxysilyl group, etc. can be used. In particular, by using a methyl-based or methylphenyl-based silicone oligomer, a thick and hard insulating layer can be formed. In addition, in consideration of the ease of forming the insulating layer, a methyl-based or methylphenyl-based one having a relatively low viscosity may be used.

[0030] The amount of silicone oligomer added is preferably 0.1 to 2.0 wt% of the Fe-Si alloy powder. If the amount added is less than 0.1 wt%, it will not function as an insulating coating, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.0 wt%, it will result in a reduced density of the powder core.

[0031] After the silicone oligomer is added, the mixture of the Fe-Si alloy powder and the silicone oligomer is heated and dried. The drying temperature is preferably 25°C to 350°C. If the drying temperature is less than 25°C, the film is not completely formed, the eddy current loss is high, and the loss increases. On the other hand, if the drying temperature is more than 350°C, the powder is oxidized, and the hysteresis loss increases, and the loss increases. The drying time is about 2 hours.

[0032] Silicone resin is a resin that has a siloxane bond (Si-O-Si) as its main skeleton. By using silicone resin, it is possible to form a coating with excellent flexibility. Silicone resin can be methyl-based, methylphenyl-based, propylphenyl-based, epoxy resin-modified, alkyd resin-modified, polyester resin-modified, rubber-based, etc. Among these, when using methylphenyl-based silicone resin in particular, it is possible to form an insulating layer with little loss on heating and excellent heat resistance.

[0033] The silicone resin is preferably added in an amount of 0.8 to 2.0 wt% based on the Fe-Si alloy powder. If the amount added is less than 0.8 wt%, it will not function as an insulating coating, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.0 wt%, it will result in a reduced density of the powder magnetic core.

[0034] After the silicone resin is added, the mixture of Fe-Si alloy powder and silicone resin is heated and dried. The drying temperature is preferably 100°C to 200°C. If the drying temperature is lower than 100°C, the formation of the insulating coating may be incomplete, resulting in high eddy current loss. On the other hand, if the drying temperature is higher than 200°C, the powder becomes inorganic and does not function as a binder, resulting in poor shape retention and a decrease in the density and magnetic permeability of the molded body. The drying time is about 2 hours.

[0035] In addition, moisture may be added when forming the insulating layer. Examples of moisture include water and ethanol. The moisture is added after mixing the soft magnetic powder with a silane coupling agent, silicone resin, etc., or at the initial stage of heating and drying the silane coupling agent, silicone resin, etc. The moisture is added by dispersing it in a mist or spray form, or by dripping it as fine water droplets. By adding moisture, the hydrolysis and condensation reactions required for the silane coupling agent, etc., are improved, and the strength of the core is improved. The moisture evaporates by heating and drying, and does not remain in the insulating layer.

[0036] A lubricant is added to the Fe-Si alloy powder surrounded by an insulating layer, and the powder core is produced through a compacting process and a compact heat treatment process. Examples of the lubricant include stearic acid and its metal salts, as well as ethylene bisstearamide, ethylene bisstearamide, and ethylene bisstearamide.

[0037] The pressure molding process is a process for producing a powder compact by pressure molding the Fe-Si alloy powder on which the insulating layer has been formed. First, the Fe-Si alloy powder is filled into a die, and then, a pressure of 10 to 20 ton / cm is applied. 2 The mixture is pressed at a pressure of 1000 psi to form a green compact.

[0038] In the compact heat treatment step, the powder compact is heat treated in a non-oxidizing atmosphere such as nitrogen gas, hydrogen gas, a mixture of nitrogen and hydrogen, or a low-oxygen atmosphere such as 0.01% oxygen atmosphere at a temperature of 650°C or higher and lower than the temperature at which the insulating layer formed around the Fe-Si alloy powder is destroyed (for example, 900°C). A powder magnetic core is produced by undergoing the heat treatment.

[0039] The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0040] First, soft magnetic powders of Example 1 and Comparative Examples 1 and 2 were prepared, and dust cores were prepared using each soft magnetic powder. Example 1 and Comparative Examples 1 and 2 differ in the presence or absence of phosphate glass on the surface of the soft magnetic powder and the type of metal bonded to the phosphate glass. Specifically, Example 1 has a compound formed by bonding Nb and phosphate glass attached to the surface of the soft magnetic powder, whereas Comparative Example 1 does not add a compound formed by bonding Nb and phosphate glass, and Comparative Example 2 has a compound formed by bonding Sn and phosphate glass attached. The rest were prepared using the same process and conditions. The soft magnetic powders and dust cores of Example 1 and Comparative Examples 1 and 2 were prepared as follows.

[0041] First, Fe-5.5% Si alloy powder was prepared and heat-treated in a nitrogen atmosphere at 650° C. for 2 hours.

[0042] In Example 1, 0.3 wt% of a compound formed by combining Nb and phosphate glass and 0.75 wt% of an acrylic binder were added to the heat-treated Fe-5.5%Si alloy powder. In Comparative Example 2, 0.3 wt% of a compound formed by combining Sn and phosphate glass and 0.75 wt% of an acrylic binder were added. In Example 1 and Comparative Example 2, heat treatment was performed for 10 hours at a temperature of 380°C in a nitrogen atmosphere. On the other hand, in Comparative Example 1, phosphate glass combined with metals such as Nb and Sn was not added, and Nb and phosphate glass were not attached to the surface of the Fe-5.5%Si alloy powder. In other words, in Comparative Example 1, the following steps were performed without performing this step.

[0043] Then, 0.5wt% of silicone oligomer was mixed with the Fe-5.5%Si alloy powder, and the mixture was dried in the air at 200°C for 2 hours. The Fe-5.5%Si alloy powder was passed through a sieve with a mesh size of 250μm in order to eliminate aggregation. The sieved Fe-5.5%Si alloy powder was mixed with 1.6wt% of silicone resin with a solid content of 50%, and dried in the air at 150°C for 2 hours. The Fe-5.5%Si alloy powder was passed through a sieve with a mesh size of 250μm in order to eliminate aggregation. As a result, in Example 1 and Comparative Example 2, a layer of silicone oligomer was formed on the outside of the Fe-5.5%Si alloy powder to which the compound of Nb or Sn and phosphate glass was attached, and further, a layer of silicone resin was laminated on the outside of the layer of silicone oligomer. On the other hand, in Comparative Example 1, a layer of silicone oligomer was formed on the surface of the Fe-5.5% Si alloy powder, and further, a layer of silicone resin was laminated on the outer side of the silicone oligomer layer.

[0044] Then, 0.5 wt% of a lubricant (Acrawax (registered trademark)) was mixed in. The soft magnetic powder to which the lubricant had been added was filled into a die and pressed to obtain powder compacts with an outer diameter of 16.5 mm, an inner diameter of 11.0 mm, and a height of 5.0 mm. The pressure for the press molding was 15 ton / cm. 2 Each powder compact was heat treated in a nitrogen atmosphere at 850°C for 2 hours.

[0045] A primary winding of 20 turns and a secondary winding of 20 turns were wound with a copper wire of φ0.5 mm around the dust cores of Example 1 and Comparative Examples 1 and 2 produced as described above, and the hysteresis loss was measured. The measurement conditions were a frequency of 100 kHz and a maximum magnetic flux density Bm=100 mT. A BH analyzer (Iwatsu Measurement Co., Ltd.: SY-8219) was used as the magnetic measuring device. The hysteresis loss coefficient and eddy current loss coefficient were calculated by the least squares method using the following equations (1) to (3), to calculate the hysteresis loss, eddy current loss, and iron loss.

[0046] Pcv = Kh × f + Ke × f2 (1) Ph = Kh × f (2) Pe = Ke × f2 (3) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Ph: Hysteresis loss Pe: Eddy current loss

[0047] The results of the measured hysteresis loss are shown in Table 1 and Fig. 1. Fig. 1 is a graph showing the hysteresis loss of Example 1 and Comparative Examples 1 and 2. [Table 1]

[0048] As shown in Table 1 and Figure 1, it was confirmed that Example 1, in which a compound of Nb and phosphate glass was added, had a reduced hysteresis loss compared to Comparative Example 1, in which no glass was added, and Comparative Example 2, in which a compound of Sn and phosphate glass was added. This is presumably because the crystal structure of the surface of the Fe-5.5%Si alloy powder became a regular structure by attaching Nb to the surface of the Fe-5.5%Si alloy powder. Therefore, it was confirmed that the hysteresis loss was reduced by attaching a compound of Nb and phosphate glass to the surface of the Fe-Si alloy powder.

[0049] Next, soft magnetic powders of Examples 2 to 5 and Comparative Examples 3 to 8 were prepared, and dust cores were prepared using each soft magnetic powder, and the hysteresis loss, eddy current loss, and iron loss were measured. As shown in Table 2 below, Examples 2 to 5 and Comparative Examples 3 to 8 differ in the particle size of the Fe-5.5%Si alloy powder used as the soft magnetic powder.

[0050] In Examples 2 to 5 and Comparative Examples 3 to 8, Fe-5.5%Si alloy powder prepared as soft magnetic powder was heat-treated in a nitrogen atmosphere at 650°C for 2 hours. The heat-treated Fe-5.5%Si alloy powder was then sieved to obtain Fe-5.5%Si alloy powders with particle sizes (median size D50) shown in Table 2 below.

[0051] In addition, in Examples 2 to 5 and Comparative Example 3, 0.3 wt% of a compound in which Nb and phosphate glass are bonded and 0.75 wt% of an acrylic binder are added to the Fe-5.5%Si alloy powder classified in the same manner as in Example 1, and the compound in which Nb and phosphate glass are bonded is adhered to the surface of the Fe-5.5%Si alloy powder. On the other hand, in Comparative Examples 4 to 8, no phosphate glass is added, as in Comparative Example 1. The rest of the samples were produced using the same steps and conditions as in Example 1 and Comparative Examples 1 and 2.

[0052] The above measurement results are shown in Table 2 and Figures 2 to 4. Figure 2 is a diagram showing the relationship between the average particle size of the soft magnetic powder and hysteresis loss. Figure 3 is a diagram showing the relationship between the average particle size of the soft magnetic powder and eddy current loss. Figure 4 is a diagram showing the relationship between the average particle size of the soft magnetic powder and iron loss.

[0053] [Table 2]

[0054] As shown in Table 2 and Figures 2 and 3, it was confirmed that adding a compound formed by combining Nb with phosphate glass reduces not only hysteresis loss but also eddy current loss, and as a result, it was confirmed that iron loss is reduced, as shown in Figure 4. This is presumably because phosphate glass adheres to the surface of the Fe-5.5%Si alloy powder and acts as an insulating coating, thereby reducing eddy current loss.

[0055] However, looking at Comparative Example 3 with an average particle size of 5.527 μm, it was confirmed that the effect of reducing hysteresis loss was difficult to obtain, even though a compound in which Nb and phosphate glass were combined was added as in Examples 2 to 5. This is a supposition and is not limited to this mechanism, but in the case of fine powder with an average particle size of 5.527 μm, it is difficult to increase the density in the first place, and the density tends to decrease. Therefore, it is thought that the effect of increasing hysteresis loss due to the decrease in density was greater than the effect of reducing hysteresis loss due to the repair of the crystal structure by Nb.

[0056] In addition, when comparing Comparative Example 3 and Comparative Example 8, both of which have an average particle size of 5.527 μm, it was confirmed that, although eddy current loss was reduced in Comparative Example 3, hysteresis loss worsened. This is also speculation, and the mechanism is not limited to this, but it is believed that the density was reduced by adding glass compared to Comparative Example 8, which did not add glass, resulting in an increase in hysteresis loss. Therefore, it was confirmed that the effect of reducing hysteresis loss can be obtained by making the average particle size 13.76 μm or more.

[0057] Finally, soft magnetic powders of Examples 6 to 14 and Comparative Examples 9 to 29 were prepared, and dust cores were produced using each soft magnetic powder. Fe-5.5%Si alloy powder was also prepared as the soft magnetic powder in Examples 6 to 14 and Comparative Examples 9 to 29. However, Fe-Si alloy powder that had been heat-treated was sieved so that the average particle size (median size D50) of the Fe-5.5%Si alloy powder was one type with a mean particle size of 13.76 μm.

[0058] As shown in Tables 3 to 5 below, the amount of compound in which Nb and phosphate glass are combined is different, with 0.3 wt% added. Furthermore, with respect to the heat treatment atmosphere after the production of the compact, the powder cores of Examples 6 to 8 and Comparative Examples 9 to 15 were heat-treated in a nitrogen atmosphere, the powder cores of Examples 9 to 11 and Comparative Examples 16 to 22 were heat-treated in a 0.01% low-oxygen atmosphere, and the powder cores of Examples 12 to 14 and Comparative Examples 23 to 29 were heat-treated in a hydrogen atmosphere. The rest of the powder cores were produced using the same steps and conditions as Example 1 and Comparative Examples 1 and 2.

[0059] The hysteresis loss, eddy current loss and iron loss were calculated using the above magnetic measuring device. The results are shown in Tables 3 to 5 and Figs. 5 to 7. Table 3 shows the results of Examples 6 to 8 and Comparative Examples 9 to 15 in which the compacts were heat-treated in a nitrogen atmosphere. Table 4 shows the results of Examples 9 to 11 and Comparative Examples 16 to 22 in which the compacts were heat-treated in a low-oxygen atmosphere. Table 5 shows the results of Examples 12 to 14 and Comparative Examples 23 to 29 in which the compacts were heat-treated in a hydrogen atmosphere. The Nb content shown in each table was derived from the analysis of a compound in which Nb and phosphate glass were combined, which revealed that the Nb content was 45%. Fig. 5 shows the relationship between the amount of the compound in which Nb and phosphate glass were combined and the hysteresis loss. Fig. 6 shows the relationship between the amount of the compound in which Nb and phosphate glass were combined and the eddy current loss. Fig. 7 shows the relationship between the amount of the compound in which Nb and phosphate glass were combined and the iron loss.

[0060] [Table 3] [Table 4] [Table 5]

[0061] As shown in Tables 4 to 6 and Figures 4 to 6, when a trace amount of a compound formed by combining Nb and phosphate glass is added, i.e., 0.01 wt%, the hysteresis loss and eddy current loss increase. However, as the amount of addition is increased, the hysteresis loss and eddy current loss decrease. When 0.1 wt% (Nb content is 0.0450 wt%) is added, the hysteresis loss is 700 (kW / m 3 It was confirmed that the iron loss was smaller than 1000 (kW / m2). And, when 0.2wt% (Nb content is 0.0900wt%) is added, the eddy current loss was also reduced, and the iron loss was 1000 (kW / m2 3 ) was lower than that in the case of the heat treatment of the compact. This tendency was the same regardless of the atmosphere in which the compact was heat treated.

[0062] On the other hand, when the amount of the compound in which Nb and phosphate glass are combined is more than 0.6wt% (Nb content is 0.2700wt%), the hysteresis loss increases and the iron loss begins to increase. Although this is a supposition and the mechanism is not limited to this, it is thought that when the amount of added is large, Nb not only repairs but also causes distortion in the crystal structure, so that the hysteresis loss increases. Therefore, it was confirmed that the amount of the compound in which Nb and phosphate glass are combined is preferably 0.1wt% or more and 0.6wt% or less (Nb content is 0.0450wt% or more and 0.2700wt% or less). It was also confirmed that this result is the same regardless of whether the heat treatment atmosphere of the molded body is nitrogen, oxygen, or hydrogen.

[0063] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.

Claims

1. Fe-Si alloy powder and an insulating layer, A compound formed by bonding Nb and phosphate glass is attached to the surface of the Fe-Si alloy powder, the insulating layer is formed on a surface of the Fe-Si alloy powder to which a compound formed by bonding the Nb and the phosphate glass is attached, The average particle size of the Fe—Si alloy powder is 13.76 μm or more in terms of median diameter D50, The amount of the compound added is 0.2 wt % or more and 0.6 wt % or less with respect to the Fe-Si alloy powder, The content of Nb in the compound is 0.090 wt % or more and 0.27 wt % or less; A soft magnetic powder characterized by:

2. Contains the soft magnetic powder according to claim 1; A powder magnetic core characterized by:

Citation Information

Patent Citations

  • High-temperature sliding material

    JP1984029819A

  • Reactor

    JP2017098426A

  • Soft magnetic composite powder and production method therefor and production method for soft magnetic compact

    WO2005015581A1